PEREMPUAN DALAM PERSPEKTIF HADIS : Keseimbangan Antara Ibadah, Akhlak, dan Hak Sosial - U. Saifuddin ASM; Ali Masrur; Tajul Arifin; Ulvah Nur’aeni (AL ISNAD: Journal of Indonesian Hadith Studies, 2025)
This study analyzes a hadith of the Prophet Muhammad ﷺ narrated by Abu Hurairah, which discusses two women with contrasting levels of ritual devotion and social behavior. The hadith serves as a crucial foundation for understanding the interrelation between ritual worship and social ethics, particularly in the context of neighborly rights (ḥuqūq al-jār) and the ethical conduct of women in Islamic society. Employing an interdisciplinary approach that integrates matn criticism, hadith commentary (sharḥ), and social-gender analysis based on the TA11 framework (comprising Tamhid, Tautsiq, Takhrij, Tanasub with the Qur’an and other hadiths, Tarikh, Tarjamah Mufradat, Tahlil Sharḥ, Ta’wil, and Tathbiq), this research reveals that piety in Islam is not solely measured by the quantity of ritual acts, but more importantly by the quality of ethical behavior in social life. The hadith affirms that a woman who was diligent in worship yet harmed her neighbors is destined for Hell, whereas another woman with fewer ritual practices but who maintained good social relations is promised Paradise. These findings emphasize the importance of a prophetic model of social piety grounded in empathy, social responsibility, and ethical communication. The study contributes significantly to rethinking the construct of Muslim women's piety in contemporary society.